Physicochemical and Antioxidant Properties of Malaysian Tualang Honey on Long Term Storage/ R. Krishna Kishore... [et al.] - Kishore, R. Krishna; Nasar, S. Abdul; Viji, P.T; Chin, Keong Lim; Halim, Ahmad Sukari (Faculty of Dentistry, 2014)
Honey is a rich source of natural nutrients. Its production is a slow, natural process with the pace of which varies seasonally. However, based on recent reports, we hypothesize that the long-term storage of processed honey, even under the most appropriate storage conditions, results in a deterioration of its quality. To test our hypothesis, we collected Tualang honey samples harvested during the years 2005, 2008, 2009 and 2010 and tested various parameters including physicochemical properties and also performed comparative analyses of antioxidant capacities to assess its medicinal values. Our results indicate that, upon long-term storage, the quality of honey samples deteriorates, as observed in our TH 2008 and TH 2005 year honey samples, which showed unacceptable quality based on the recommended criteria of free acidity (71.34±1.31 meq/kg), moisture (27.72%), diastase activity (3.38±0.34 Goth scale) and hydroxymethylfurfural (HMF) (449.89±3.23 mg/kg) by Codex and European Commission Regulation. A significant (p<0.05) decrease in antioxidant properties were also observed. In the present study, we show that, even after appropriate processing, most of the quality parameters of honey decrease, which suggest that these parameters could otherwise be used as markers to assess the age of the honey.